2014
DOI: 10.3109/03630269.2014.978455
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Molecular Diagnosis of β-Thalassemia and Sickle Cell Anemia in the Syrian Population

Abstract: Our objective was to evaluate the prenatal diagnosis (PND) of β-thalassemia (β-thal) and sickle cell anemia in Syria. Mutations detected from blood of at-risk couples and 55 amniotic fluid samples collected at the second trimester of pregnancy (14-22 weeks' gestation) were characterized. Molecular screening and direct DNA sequencing of the HBB gene was carried out. DNA analyses showed 14 affected fetuses (25.45%), 32 (58.18%) carriers and eight (14.54%) normal fetuses. It appears that 20.0% of individuals carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…mutations is not identical throughout all regions in Syria. There were previously published studies on the spectrum of β-globin gene mutations in the Syrian population, the authors did not indicate the distribution of the mutations to different parts of the country because the number of studied alleles was insufficient for mapping the distribution of mutations along the country [9,10,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mutations is not identical throughout all regions in Syria. There were previously published studies on the spectrum of β-globin gene mutations in the Syrian population, the authors did not indicate the distribution of the mutations to different parts of the country because the number of studied alleles was insufficient for mapping the distribution of mutations along the country [9,10,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…The eight most common β-globin gene defects in previous studies [9,10] were examined by the amplification refractory mutations system-polymerase chain reaction (ARMS-PCR) technique [11]. ARMS primers were selected from Old [12].…”
Section: Amplification Refractory Mutation Systempolymerase Chain Reamentioning
confidence: 99%
“…The aim of retinopathy screening is to detect PSR and consider treatment for example photocoagulation before complications, such as VH or TRD or retinal vascular occlusions with visual loss occur. In terms of diagnostic screening, DNA screening in newborns at risk, for example with a positive family history of SCD, has been suggested [38,39].…”
Section: Screeningmentioning
confidence: 99%
“…It is believed that codon 39 (C> T) is of Roman origin, and has a high prevalence in Sardinia, mainland Italy, Spain, Portugal and Tunisia (19). Different studies also found this mutation to be frequent in Venezuela (18), Northern Greece (20), Syria (21), and confirmed it in Tunisia (22) and Italy (23).…”
mentioning
confidence: 76%
“…The next most common 0 thalassemia mutation in our cohort, IVS-I-1, shows a restricted geographical distribution in Eastern Mediterranean countries (Syria, Lebanon, Jordan, Palestine and Egypt) (21).…”
mentioning
confidence: 83%